2017
DOI: 10.1371/journal.pone.0174608
|View full text |Cite
|
Sign up to set email alerts
|

Correction of vitamin D deficiency facilitated suppression of IP-10 and DPP IV levels in patients with chronic hepatitis C: A randomised double-blinded, placebo-control trial

Abstract: Vitamin D deficiency was common among patients with chronic hepatitis C (CHC) and had negative influence on treatment outcome. Correction of vitamin D deficiency improved treatment response. Interferon gamma-induced protein 10 (IP-10) and enzyme dipeptidyl peptidase-4 (DPP IV) involved in inflammatory responses in CHC. Their higher levels at pretreatment of CHC could predict poorer responses. Vitamin D suppressed expression of IP-10 from monocytes in vitro. In CHC patients, DPP IV involved in IP-10 regulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Optimal vitamin D levels may attenuate this virulent mechanism. In vivo studies have shown that the expression of DPP4/CD26 was significantly reduced after the correction of 25(OH)D deficiency [ 104 ]. These findings suggest that vitamin D supplementation is promising for the management of this new viral disease.…”
Section: Vitamins and Immune Systemmentioning
confidence: 99%
“…Optimal vitamin D levels may attenuate this virulent mechanism. In vivo studies have shown that the expression of DPP4/CD26 was significantly reduced after the correction of 25(OH)D deficiency [ 104 ]. These findings suggest that vitamin D supplementation is promising for the management of this new viral disease.…”
Section: Vitamins and Immune Systemmentioning
confidence: 99%
“…Some of the unique residues of S1 domain of COVID-19 spike glycoprotein are also presumed to interact with the ACE2 protein [ 58 ]. The expression of the DPP-4/CD26 receptor has been shown to be reduced significantly in vivo upon the correctness of vitamin D insufficiency [ 59 ]. However, there is insufficient evidence to elucidate the effect, if any, of sustained DPP-4 inhibition (as can be achieved through the correction of vitamin D insufficiency or through the use of DPP-4 inhibitors used in the treatment of diabetes) on coronavirus infections.…”
Section: Mechanism Behind Vitamin D’s Possible Protective Role Againsmentioning
confidence: 99%
“…Additionally, low serum VD levels were related to severe histological features and potentially predicted unfavorable treatment outcomes in patients with autoimmune hepatitis [ 29 ]. Among CHC patients, VD deficiency has several detrimental effects, including dysregulation of T-cell functions, resulting in lower response rates of the HCV genotype 1 to pegylated interferon and RBV treatment [ 14 , 30 ]. However, the revolutionization of HCV treatment with DAA has improved the overall curative rate to nearly 100% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%